ANALISIS KEBUTUHAN NASABAH ATAS FITUR APLIKASI BIMA MOBILE PADA PT BANK PEMBANGUNAN DAERAH JAWA TENGAH - Damayanti, Hamida; Sunindyo, Aris; Wahyuni, Mirasanti (KEUNIS, 2023)
Intense market competition can affect customer responses to bank performance. Bank need customer responses to their products or services so that they can be used as material for evaluation and improvement in the future. Customer needs continue to change and increasingly diverse in line with development in the world and technology, so companies must be able to meet the needs desired by customers. The purpose of this research is to determine customer responses to the current Bima Mobile service and customer needs for the availability of Bima Mobile application features. In this research the descriptive statistical measurement used is the mean of customer response data and customer needs which have been arranged in a frequency distribution table. The analysis results show that the lowest indicator on the customer response component is occupied by the feature availabilityr, while the highest is application display. For the customer needs component, the analysis results show that the lowest indicator is the availability of the donation payment feature and the highest is the availability of the electricity payment feature. The company can take steps to follow up on customer responses to the features avaibility indicator that occupies the lowest position, by developing the Bima Mobile application features availability according to customer needs.